Stem Cell Therapy in Injured Vocal Folds: A Three-Month Xenograft Analysis of Human Embryonic Stem Cells. (18th October 2015) - Svensson, Bengt; Nagubothu, Srinivasa R.; Nord, Christoffer; Cedervall, Jessica; Hultman, Isabell; Ährlund-Richter, Lars; Tolf, Anna; Hertegård, Stellan
Abstract : We have previously shown that human embryonic stem cell (hESC) therapy to injured rabbit vocal folds (VFs) induces human tissue generation with regained VF vibratory capacity. The aims of this study were to test the sustainability of such effect and to what extent derivatives of the transplanted hESCs are propagated in the VFs. The VFs of 14 New Zealand rabbits were injured by a localized resection. HESCs were transplanted to 22 VFs which were analyzed for persistence of hESCs after six weeks and after three months. At three months, the VFs were also analyzed for viscoelasticity, measured as dynamic viscosity and elastic modulus, for the lamina propria (Lp) thickness and relative content of collagen type I. Three months after hESC cell therapy, the dynamic viscosity and elastic modulus of the hESC treated VFs were similar to normal controls and lower than untreated VFs (p ≤ 0.011 ). A normalized VF architecture, reduction in collagen type I, and Lp thickness were found compared with untreated VFs (p ≤ 0.031 ). At three months, no derivatives of hESCs were detected. HESCs transplanted to injured rabbit VFs restored the vibratory characteristics of the VFs, with maintained restored function for three months without remaining hESCs or derivatives.